A Review on Melt-Pool Characteristics in Laser Welding of Metals - Behzad Fotovvati; Steven F. Wayne; Gladius Lewis; Ebrahim Asadi (Advances in Materials Science and Engineering)
Laser welding of metals involves with formation of a melt-pool and subsequent rapid solidification, resulting in alteration of properties and the microstructure of the welded metal. Understanding and predicting relationships between laser welding process parameters, such as laser speed and welding power, and melt-pool characteristics have been the subjects of many studies in literature because this knowledge is critical to controlling and improving laser welding. Recent advances in metal additive manufacturing processes have renewed interest in the melt-pool studies because in many of these processes, part fabrication involves small moving melt-pools. The present work is a critical review of the literature on experimental and modeling studies on laser welding, with the focus being on the influence of process parameters on geometry, thermodynamics, fluid dynamics, microstructure, and porosity characteristics of the melt-pool. These data may inform future experimental laser welding studies and may be used for verification and validation of results obtained in future melt-pool modeling studies.